PERBANDINGAN EFEKTIVITAS PENGENDALIAN ROBOT DENGAN PENGGUNAAN PID DAN TANPA PID PADA APLIKASI JARAK TERTENTU - Habibi, Aazamzain; Suksmadana, I Made Budi; Darmawan, Budi (Jurnal Informatika Teknologi dan Sains (Jinteks), 2024)
A mobile robot is a type of robot that uses a wheel or leg-based propulsion system to move efficiently. This robot is highly beneficial in various industries, particularly in improving operational efficiency through autonomous movement. This research aims to examine the performance of the PID control on an encoder-based robot and evaluate its effectiveness compared to a system without PID. The research method includes designing a robot powered by a 18650 battery as the main power source, with an L298N motor driver and a DC N20 motor with an encoder connected to an Arduino microcontroller as the primary controller. An SD card module and a buck converter are also used to store operational data and regulate voltage to ensure stability. In this study, the robot's performance is tested at various distances, both with and without PID control. The test results show that without PID, the robot deviates more from the target, especially at longer distances, such as 220 cm. In contrast, with PID control, the robot is able to reach the target with higher accuracy and more controlled deviation. The use of PID also reduces variation in time and distance traveled, as well as enhances system stability.